(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Recent studies of Erwinia amylovora in Montenegro, conducted from 2012 to 2014, indicated that the bacterium was widespread in the northern, continental part of the country, where the most important fruit-growing regions are situated. The presence of the bacterium was confirmed on quince, pear, apple, medlar and hawthorn. Pathogenic, cultural and biochemical characteristics of E. amylovora strains sampled from pome fruit species and indigenous flora in Montenegro had been studied previously. In the present study, serological tests were used for identification of E. amylovora strains originating from pome fruit trees and indigenous plants. Monitoring of E. amylovora and collection of samples with symptoms of bacterial fire blight from different hosts and locations were performed in Montenegro from 2012 to 2014. Isolation of the bacterium on nutrient medium produced a large number of isolates, whose pathogenicity was confirmed on immature pear fruits. Twenty-seven strains of the bacterium, originating from three pome fruit species (quince, pear and apple) and one indigenous species (hawthorn) were selected for serological analyses. Two applied serological methods, ELISA and IF test, enabled rapid detection of the bacterium and simultaneous examination of a large number of samples over a short period of time. Serological analyses showed high homogeneity in antigenic structure of the studied E. amylovora strains sampled from quince, pear, apple and hawthorn from nine locations in Montenegro.